Cognitive–behavioural suicide prevention for male prisoners: a pilot randomized controlled trial. Issue 16 (13th July 2015) - Pratt, D.; Tarrier, N.; Dunn, G.; Awenat, Y.; Shaw, J.; Ulph, F.; Gooding, P.
Abstract : Background: Prisoners have an exceptional risk of suicide. Cognitive–behavioural therapy for suicidal behaviour has been shown to offer considerable potential, but has yet to be formally evaluated within prisons. This study investigated the feasibility of delivering and evaluating a novel, manualized cognitive–behavioural suicide prevention (CBSP) therapy for suicidal male prisoners. Method: A pilot randomized controlled trial of CBSP in addition to treatment as usual (CBSP; n = 31) compared with treatment as usual (TAU; n = 31) alone was conducted in a male prison in England. The primary outcome was self-injurious behaviour occurring within the past 6 months. Secondary outcomes were dimensions of suicidal ideation, psychiatric symptomatology, personality dysfunction and psychological determinants of suicide, including depression and hopelessness. The trial was prospectively registered (number ISRCTN59909209). Results: Relative to TAU, participants receiving CBSP therapy achieved a significantly greater reduction in suicidal behaviours with a moderate treatment effect [Cohen's d = −0.72, 95% confidence interval −1.71 to 0.09; baseline mean TAU: 1.39 (s.d. = 3.28) v . CBSP: 1.06 (s.d. = 2.10), 6 months mean TAU: 1.48 (s.d. = 3.23) v. CBSP: 0.58 (s.d. = 1.52)]. Significant improvements were achieved on measures of psychiatric symptomatology and personality dysfunction. Improvements on psychological determinants of suicide were non-significant. More than half of the participants in the CBSP group achieved a clinically significant recovery by the end of therapy, compared with a quarter of the TAU group. Conclusions: The delivery and evaluation of CBSP therapy within a prison is feasible. CBSP therapy offers significant promise in the prevention of prison suicide and an adequately powered randomized controlled trial is warranted.